Utilizing iPad in TEYL: Some benefits and barriers - Sari, Preti Maha (International Islamic Schools Alliance, 2023)
At present, tablet devices are used in teaching in the schools across the nation, the most popular device is iPad and the role of teachers in using technology especially iPad is very crucial to serve the learners in order to make them learn better in a fun way. The objective of this study was to investigate the use of the iPad for teaching and learning in terms of benefits and the barriers through the experiences of classroom teachers and students in one of Primary School in Palembang, Indonesia. Qualitative methods, including teacher and student-participant interviews, classroom observations, and document review were utilized in this study. The purposefully selected sample consisted of three primary English teachers and two students grade 6 who were used iPad for teaching and learning. The research revealed that the use of iPad for teaching English for young learners was good. It had some advantages that support student learning and teacher teaching. However, despite the positive sides of using iPad, teachers and students faced numerous barriers, such as technical problem, lack of proper skill, and others.